1988
DOI: 10.1172/jci113732
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor inhibits the hydroosmotic effect of vasopressin in the isolated perfused rabbit cortical collecting tubule.

Abstract: Epidermal growth factor (EGF) is a 53-amino acid polypetide which is a potent mitogen for cultured cells. The kidney has recently been shown to be a major site of synthesis for the EGF precursor. EGF infusions in sheep result in a diuresis and natriuresis despite a fall in GFR, suggesting a direct tubular effect. Using in vitro microperfusion of rabbit cortical collecting tubules (CC1s) at 370C, we examined the effect of EGF on the transepithelial voltage (VJ) and arginine vasopressin (AVP)-stimulated hydrauli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 45 publications
3
39
0
Order By: Relevance
“…In the mouse submaxillary gland, prepro-EGF is processed intracellularly to the 53-amino acid form of the peptide. In contrast, in kidney cells the precursor accumulates and is not processed to mature EGF (17,20 liii.-.~~_ age of the extracellular membrane-bound protein by proteases present in the lumen ofthe nephron or in serum would serve to release EGF and account for the large quantity of the peptide present in urine (7) or in medullary interstitium (17,20 (12,21) and in freshly isolated suspensions (22). Teitelbaum et al (12) reported that EGF stimulates phospholipase C activity in cultured rat inner medullary collecting tubule cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse submaxillary gland, prepro-EGF is processed intracellularly to the 53-amino acid form of the peptide. In contrast, in kidney cells the precursor accumulates and is not processed to mature EGF (17,20 liii.-.~~_ age of the extracellular membrane-bound protein by proteases present in the lumen ofthe nephron or in serum would serve to release EGF and account for the large quantity of the peptide present in urine (7) or in medullary interstitium (17,20 (12,21) and in freshly isolated suspensions (22). Teitelbaum et al (12) reported that EGF stimulates phospholipase C activity in cultured rat inner medullary collecting tubule cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…The action of VP to increase water permeability of the collecting duct is modulated by a number of hormones and autacoids, including prostaglandin E 2 (PGE 2 ), endothelin, cholinergic agents, and epidermal growth factor, [37][38][39][40] which act through different pathways. Cellular pathways known to be involved in the inhibition of VP signaling are protein kinase C and the extracellularly regulated protein kinases.…”
Section: Factors In the Control Of Water Excretionmentioning
confidence: 99%
“…and AVP are physiological ligands of principal cells that exert antagonistic hydroosmotic effects on the collecting duct (30,31). We therefore tested the ability of these factors to regulate the expression of MMP2 and MMP9 in RC.SVtsA58 cells.…”
Section: Mmp9 Is Differentially Regulated By Physiological Ligands Ofmentioning
confidence: 99%
“…It also raises sodium reabsorption by apical epithelial sodium channels (54). EGF inhibits the hydroosmotic effects of AVP by acting at a post-cAMP level (30). Conversely, AVP inhibits the EGF-stimulated mitogen-activated protein kinase cascade (55), indicating that the signal transduction pathways of AVP and EGF are closely connected in collecting duct cells.…”
Section: Fig 5 Northern Blot Analysis Of Large-t Egf (15 Ng/ml) Amentioning
confidence: 99%